TINGKAT KONDISI FISIK TIM NASIONAL FLOORBALL PADA KEJUARAAN ASIA OCEANIA FLOORBALL COMPETITION (AOFC) - Saepuloh, Epul; Pramdhan , Kartono (STKIP Pasundan, 2017)
This study aims to determine the level of physical condition of the floorbal national team at the Asia Oceania Floorball Competition (AOFC) championship. The method used in this study is a survey method with a total of 20 players from the Indonesian National Floorball Team. With a total sample of 20 people. The sample used is saturated sampling. Based on the results of data processing and data analysis that can be described in the component speed (speed) is classified as having a good ability of 100% overall 65% good players. In the agility component, 100% of the National Team floorball players are 80% less and only 15% are good. Components of 85% players are categorized as perfect. In the Anaerobic component 75% of the players are categorized very well and in the Aerob component of 100% the players 70% of the national team players are very good. Based on the overall data above, it can be seen that the Physical Condition Level of the Floorball National Team has a good physical condition because the acquisition of the largest percentage of all physical components is 18 players or 90% of the 20 Floorball National Team players are categorized as good.